Implementasi Metode Kibar dalam Meningkatkan Kemampuan Membaca Al-Quran di TPQ Baitul Muttaqin Kota Padang (Tazakka: Jurnal Pendidikan dan Keislaman, 2024)
This research is motivated by the problems that arise in Quran learning for children at TPQ. The Quran Student has called by santri. There is problems with improper pronunciation of makharij al-hurf and also the level of laziness of children to learn the Quran, especially in an era dominated by increasingly sophisticated technology like cell phones, which results in children being less fluent in reading the Quran, so a method of learning the Quran that is by the development and growth of children at this time is applied, namely the Kibar method. The Kibar method is the development of the iqra method which is presented in a more concise, simple and fun form consisting of three series, namely Kibar A, Kibar B and Kibar C. The speciality of this Kibar method is the arrangement of letters that are almost the same shape and sound at the beginning of the lesson, so that children are sensitive to the differences between these letters, another speciality lies in Kibar C which has provided an explanation of tajweed. The purpose of this study is to implement the Kibar method to improve the ability of santri to read the Quran. This research uses qualitative methods with the type of field research. The techniques to collecting data were carried out through interviews, observation and documentation. The results showed that the use of the kibar method at TPQ is effective because it makes students able to read the Quran in a relatively short time and have good and correct pronunciation and the Kibar method does not make santri bored. The proof is that the santris are competing in their ability so that they can continue to the next series of Kibar Method.
Keywords: Kibar Method; Santri; Reading the Quran